Red perovskite quantum dot with high luminescence property and application thereof

By doping metal elements into the core of the red perovskite quantum dots and building an isocyanate atmosphere in the shell, the problem of insufficient luminescence spectral shift and stability of perovskite quantum dots in the prior art under environmental stimulation is solved, and the improvement of high luminescence performance and multiple stability is achieved.

CN119552657APending Publication Date: 2025-03-04WENZHOU XINXIN TAIJING TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410114633.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-26
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing red perovskite quantum dots based on bromine-iodine mixed halogen are prone to halogen ions migration under environmental stimulation such as heating and strong light irradiation, resulting in a luminescence spectrum shift and insufficient water, light and thermal stability.

Method used

By doping metal elements into the core of perovskite quantum dots, perovskite nanocrystals with doped metal elements are formed, and an isocyanate atmosphere is constructed in the shell, and the quantum dots are encapsulated using micro/mesoporous templates to improve their stability.

Benefits of technology

The high luminescence performance of red perovskite quantum dots is achieved, the migration of halogen ions is inhibited, and the stability of water, light and thermal is improved, so that the luminescence spectrum does not move or deform under blue light irradiation, and the recovery rate of the luminescence intensity reaches at least 80% during the heating and cooling process of 130°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552657A_ABST
    Figure CN119552657A_ABST
Patent Text Reader

Abstract

The invention provides a red perovskite quantum dot with high luminescence property, the red perovskite quantum dot is composed of an inner core and a shell layer coating the inner core, the inner core is perovskite nanocrystal doped with metal elements, the structural formula of the perovskite nanocrystal is CsPbIxBr3-x, and X is more than 0 and less than 3; the shell layer is a micro / mesoporous template; the atomic percent of cesium is recorded as A; the atomic percent of the doped metal element is recorded as B, and B / (A + B) is 0.35-0.45; the in-situ normalized luminous intensity of the quantum dots can be recovered to at least 80% after the quantum dots are subjected to a 130-DEG C heating stage and a 130-DEG C cooling stage. The halogen ion migration problem and the stability problem are solved at the same time, and therefore the requirements of the light-emitting display field are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite materials, and in particular relates to a red perovskite quantum dot with high luminescence performance and an application thereof. Background Art

[0002] The biggest problems with existing red perovskite quantum dots based on bromine-iodine mixed halogens come from two aspects: on the one hand, due to the presence of bromine and iodine components, mixed halogen perovskites are prone to halogen ion migration under external environmental stimuli such as heating and strong light irradiation, resulting in a shift in the luminescence spectrum; on the other hand, there is water and thermal stability.

[0003] Our company's previously applied Chinese patent number ZL 202311251027.3 discloses a red perovskite quantum dot with high luminescence performance and its preparation method. This method can solve the technical problem of halogen ion migration leading to luminescence spectrum shift. However, the above method does not solve the problems of water, light and thermal stability.

[0004] In addition, in the prior art, in order to improve the stability of perovskite quantum dots, micro / mesoporous templates are usually used to encapsulate perovskite quantum dots to solve the problem of water stability, such as CN110734758 B. The micro / mesoporous template is calcined at high temperature (300-2000°C) to collapse and encapsulate the perovskite quantum dots, thereby isolating water and oxygen. However, due to the problem of too high calcination temperature, it is difficult to stabilize the lattice of quantum dots by introducing ligands to improve their QY, dry heat resistance and other properties, so it needs to be improved. Summary of the invention

[0005] The purpose of the present invention is to provide a red perovskite quantum dot with high luminescence performance and its application, by simultaneously solving the halogen ion migration problem and stability problem of the bromine-iodine mixed halogen red perovskite quantum dot, thereby meeting the industrialization demand of the perovskite quantum dot in the field of luminescent display.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a red perovskite quantum dot with high luminescence performance, composed of a core and a shell layer covering the core, the core is a perovskite nanocrystal doped with a metal element, and the structural formula of the perovskite nanocrystal is CsPbI x Br 3-x , wherein 0<X<3; the shell layer is a micro / mesoporous template; the atomic percentage of cesium is recorded as A; the atomic percentage of the doped metal element is recorded as B, and the calculation formula for the doping amount of the doped metal element at the A position is: B / (A+B)=0.35-0.45; the in-situ normalized luminescence intensity of the quantum dots after undergoing a 130°C heating stage and a cooling stage can be restored to at least 80%.

[0007] Furthermore, the doping metal element is one or more of zinc, potassium, aluminum, magnesium, calcium, strontium, barium, sodium, rubidium, lithium, cerium, samarium, antimony, erbium, and bismuth.

[0008] Furthermore, the luminescence half-width of the quantum dots is less than 40 nm, and there is only one luminescence peak, and the luminescence spectrum does not move or deform under blue light irradiation.

[0009] Further, the micro / mesoporous template comprises a microporous material or a mesoporous material;

[0010] The microporous material is one or more of microporous molecular sieve, microporous silica, microporous titanium dioxide, microporous alumina, microporous transition metal oxide, microporous sulfide, microporous silicate, microporous aluminate or microporous transition metal nitride;

[0011] The mesoporous material is one or more of mesoporous molecular sieve, mesoporous silica, mesoporous titania, mesoporous alumina, mesoporous carbon, mesoporous transition metal oxide, mesoporous sulfide, mesoporous silicate, mesoporous aluminate or mesoporous transition metal nitride.

[0012] Furthermore, it also includes an isocyanate atmosphere located in the shell layer.

[0013] Furthermore, the in-situ normalized luminescence intensity of the quantum dots after undergoing a 130° C. heating stage and a cooling stage can be restored to at least 90%.

[0014] Furthermore, the isocyanate atmosphere is generated by an isocyanate precursor at a high temperature, and the temperature range of the high temperature is greater than the collapse temperature of the micro / mesoporous template.

[0015] A perovskite quantum dot masterbatch, wherein the perovskite quantum dot masterbatch comprises the above-mentioned red perovskite quantum dots.

[0016] A perovskite quantum dot diffusion plate, comprising the above-mentioned red perovskite quantum dots.

[0017] A perovskite quantum dot film, comprising the above-mentioned red perovskite quantum dots.

[0018] The beneficial effects of the present invention are mainly reflected in:

[0019] 1. The present invention performs doping on perovskite quantum dots, introduces more doping metal elements, and simultaneously reduces the cesium content, so that the doping amount of the doping metal element reaches the range of 0.35-0.45. At this time, the red light perovskite material has only one luminescence peak, and the luminescence spectrum does not move or deform under blue light irradiation, which plays a role in inhibiting the migration of halogen ions. It has the advantages of uniform composition and no ion migration.

[0020] 2. The present application constructs an isocyanate atmosphere in the shell layer, thereby improving the PLQY and thermal stability of quantum dots. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is an in-situ normalized luminescence intensity diagram of the perovskite quantum dots obtained in Example 1 after undergoing a 130° C. heating stage and a cooling stage;

[0022] Figure 2 This is an in-situ normalized luminescence intensity diagram of the perovskite quantum dots obtained in Example 2 after undergoing a 130° C. heating stage and a cooling stage;

[0023] Figure 3 The perovskite quantum dots obtained in Comparative Example 2 were illuminated at 350 mW / cm 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum before and after the blue light irradiation was obtained;

[0024] Figure 4 The perovskite quantum dots obtained in Comparative Example 3 were 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum before and after the blue light irradiation was obtained;

[0025] Figure 5 This is an in-situ normalized luminescence intensity diagram of the perovskite quantum dots obtained in Comparative Example 1 after undergoing a 130°C heating stage and a cooling stage. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific implementation methods described herein are only used to explain the present invention and are not used to limit the present invention.

[0027] Embodiment 1:

[0028] Cb x I 3-x @MCM-41 quantum dots preparation: weigh 0.2 mol Cs 2 CO 3 、0.2mol PbBr 2 、0.2molPbI 2 、0.01mol ZnBr 2 100 g MCM-41 and 8 g cyanuric acid were mixed in a wall breaking machine for 30 seconds, taken out, and put into a sintering device. In an argon atmosphere, the temperature was raised to 630°C at a rate of 18°C / min, and then kept at 630°C for 30 minutes, and then cooled naturally to obtain CsPbBr x I 3-x @MCM-41 composite material crude product.

[0029] CsPbBr x I 3-x The crude product of @MCM-41 quantum dots was washed twice with deionized water, centrifuged and placed in a 60°C vacuum drying oven for 24 hours to obtain the purified CsPbBr x I 3-x @MCM-41 quantum dots. The energy spectrum of perovskite quantum dots measured by EDS, and the doping amount of doped metal element Zn is calculated. Then: B / (A+B)=0.42.

[0030] Experimental analysis: Take the perovskite quantum dots obtained by sintering as above and use 350mW / cm 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum was tested before and after the blue light irradiation. The luminescence spectrum did not move or deform. x I 3-x @MCM-41 quantum dot composite material has a maximum emission wavelength of 624nm and a PLQY (photoluminescence efficiency) of 70%.

[0031] like Figure 1 The thermal stability test diagram of perovskite quantum dots shown in the figure shows that the in-situ normalized luminescence intensity of the quantum dots can be restored to at least 80% after undergoing a 130°C heating stage and a cooling stage.

[0032] Embodiment 2:

[0033] Cb x I 3-x @MCM-41 quantum dots preparation: weigh 0.2 mol Cs 2 CO 3 、0.2mol PbBr 2 、0.2molPbI 2 、0.01mol ZnBr 2 100 g MCM-41 and 12 g cyanuric acid were mixed in a wall breaking machine for 30 seconds, taken out, and put into a sintering device. In an argon atmosphere, the temperature was raised to 630°C at a rate of 18°C / min, and then kept at 630°C for 30 minutes, and then cooled naturally to obtain CsPbBr x I 3-x @MCM-41 composite material crude product.

[0034] CsPbBr x I 3-x The crude product of @MCM-41 quantum dots was washed twice with deionized water, centrifuged and placed in a 60°C vacuum drying oven for 24 hours to obtain the purified CsPbBr x I3-x @MCM-41 quantum dots.

[0035] Use 350mW / cm 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum was tested before and after the blue light irradiation. The luminescence spectrum did not move or deform. x I 3-x @MCM-41 quantum dot composite material has a maximum emission wavelength of 619nm and a PLQY (photoluminescence efficiency) of 74%.

[0036] like Figure 2 The thermal stability test diagram of perovskite quantum dots shown in the figure shows that the in-situ normalized luminescence intensity of the quantum dots can be restored to at least 90% after undergoing a 130°C heating stage and a cooling stage.

[0037] Embodiment 3:

[0038] Weigh 0.2 mol Cs 2 CO 3 、0.2mol PbBr 2 、0.2molPbI 2 , 0.02mol ZnBr 2 , 100g MCM-41, and 8g cyanuric acid were mixed with a wall breaking machine for 30s, taken out, and put into a sintering device. In an argon atmosphere, the temperature was raised to 630℃ at a rate of 18℃ / min, and then kept at 630℃ for 30min, and naturally cooled to obtain CsPbBr x I 3-x @MCM-41 composite material crude product.

[0039] CsPbBr x I 3-x The crude product of @MCM-41 quantum dots was washed twice with deionized water, centrifuged and placed in a 60°C vacuum drying oven for 24 hours to obtain the purified CsPbBr x I 3-x @MCM-41 quantum dots. The energy spectrum of perovskite quantum dots measured by EDS, and the doping amount of doped metal element Zn is calculated. Then: B / (A+B)=0.45. With 350mW / cm 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum was tested before and after the blue light irradiation. The luminescence spectrum did not move or deform. The PLQY (photoluminescence efficiency) was 71%.

[0040] Embodiment 4:

[0041] Weigh 0.2 mol Cs 2 CO 3、0.2mol PbBr 2 、0.2molPbI 2 、0.006mol ZnBr 2 100 g MCM-41 and 8 g cyanuric acid were mixed in a wall breaking machine for 30 seconds, taken out, and put into a sintering device. In an argon atmosphere, the temperature was raised to 630°C at a rate of 18°C / min, and then kept at 630°C for 30 minutes, and then cooled naturally to obtain CsPbBr x I 3-x @MCM-41 composite material crude product.

[0042] CsPbBr x I 3-x The crude product of @MCM-41 quantum dots was washed twice with deionized water, centrifuged and placed in a 60°C vacuum drying oven for 24 hours to obtain the purified CsPbBr x I 3-x @MCM-41 quantum dots. The energy spectrum of perovskite quantum dots measured by EDS, and the doping amount of doped metal element Zn is calculated. Then: B / (A+B)=0.35. With 350mW / cm 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum was tested before and after the blue light irradiation. The luminescence spectrum did not move or deform. The PLQY (photoluminescence efficiency) was 67%.

[0043] Embodiment 5:

[0044] Weigh 0.2 mol Cs 2 CO 3 、0.2mol PbBr 2 、0.2molPbI 2 、0.1mol ZnBr 2 , 100g MCM-41, and 8g cyanuric acid were mixed with a wall breaking machine for 30s, taken out, and put into a sintering device. In an argon atmosphere, the temperature was raised to 630℃ at a rate of 18℃ / min, and then kept at 630℃ for 30min, and naturally cooled to obtain CsPbBr x I 3-x @MCM-41 composite material crude product.

[0045] CsPbBr x I 3-x The crude product of @MCM-41 quantum dots was washed twice with deionized water, centrifuged and placed in a 60°C vacuum drying oven for 24 hours to obtain the purified CsPbBr x I 3-x@MCM-41 quantum dots. The energy spectrum of perovskite quantum dots measured by EDS, and the doping amount of doped metal element Zn is calculated. Then: B / (A+B)=0.45. With 350mW / cm 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum was tested before and after the blue light irradiation. The luminescence spectrum did not move or deform. The PLQY (photoluminescence efficiency) was 71%.

[0046] Embodiment 6:

[0047] The difference from Example 1 is that the doped metal precursor is selected from other metal halides. The metal halide can be zinc iodide, potassium bromide, potassium iodide, aluminum chloride, aluminum bromide, sodium bromide, rubidium bromide, lithium bromide, calcium bromide, barium bromide, strontium bromide, cerium bromide, samarium bromide, antimony bromide, erbium bromide, bismuth bromide, etc. Although the doped metal precursors are different, their B / (A+B) is still in the range of 0.35-0.45. Using 350mW / cm 2 The sample was irradiated with blue light (wavelength 450nm) for 1 hour, and its photoluminescence spectrum was tested before and after the blue light irradiation. The luminescence spectrum did not move or deform.

[0048] Comparative Example 1:

[0049] The difference from Example 1 is that cyanuric acid is not added. The energy spectrum of the perovskite quantum dots measured by EDS is used to calculate the doping amount of the doped metal element Zn. Then: B / (A+B)=0.42. Using 350mW / cm 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum was tested before and after the blue light irradiation. The luminescence spectrum did not move or deform. The PLQY (photoluminescence efficiency) was 50%. CsPbBr x I 3-x @MCM-41 quantum dot composite material has a maximum emission wavelength of 631nm.

[0050] like Figure 5 The thermal stability test diagram of perovskite quantum dots shown in the figure shows that the in-situ normalized luminescence intensity of the quantum dots can be restored to 62% after undergoing a 130°C heating stage and a cooling stage.

[0051] Comparative Example 2:

[0052] The difference from Example 1 is that no ZnBr is added 2 .

[0053] Use 350mW / cm 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum ( Figure 3As shown in the figure, the luminescence spectrum changes from a single peak to a double peak, indicating that blue light aging conditions will cause ion migration, resulting in a shift in the luminescence spectrum.

[0054] Comparative Example 3:

[0055] The difference from Example 1 is that cesium carbonate is replaced by cesium halide. The cesium halide is specifically CsBr and CsI, and the molar ratio of CsBr to CsI is 1:1.

[0056] Experimental analysis: Take the perovskite powder obtained by sintering above and use 350mW / cm 2 The blue light (wavelength 450nm) was irradiated for 1 hour, and the photoluminescence spectrum ( Figure 4 As shown in Figure 2, the luminescence spectrum changes from a single peak to a double peak, indicating that ion migration will occur under blue light aging conditions, resulting in a shift in the luminescence spectrum. The energy spectrum of the perovskite quantum dots measured by EDS is used to calculate the doping amount of the doped metal element Zn. Then: B / (A+B)=0.27.

[0057] The present invention selects cesium carbonate as the cesium source precursor, which is easily decomposed into carbon dioxide and cesium oxide at high temperature. Due to the chemically active characteristics of cesium oxide, the cesium source and the metal halide are fully reacted to form perovskite, and the uniformity of the solid-state reaction is enhanced. The inhomogeneity of the perovskite composition caused by insufficient local reaction is avoided, and the doped metal is more easily introduced into the structure of the perovskite material.

[0058] In addition, the present invention uses cyanuric acid as an isocyanic acid precursor. Under the high-temperature calcination process of the present application, cyanuric acid is depyrized to produce isocyanic acid. In the specific calcination process, cyanuric acid is first heated to volatilize and sublimate into a vapor state. Since cyanuric acid first volatilizes and becomes a gaseous state, the rich pores of the micro / mesoporous template can adsorb gaseous cyanuric acid. At this time, the cyanuric acid vapor is further heated to decompose into isocyanic acid. Then, when the temperature is raised and heated to the collapse temperature of the micro / mesoporous template, the micro / mesoporous template begins to gradually collapse, close the pores, and form a shell.

[0059] The embodiments described above provide a detailed description of the preparation scheme of the present invention. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A red perovskite quantum dot with high luminescence performance, comprising a core and a shell layer covering the core, characterized in that: The core is a perovskite nanocrystal doped with a metal element, and the structural formula of the perovskite nanocrystal is CsPbI x Br 3-x , wherein 0<X<3; the shell layer is a micro / mesoporous template; The atomic percentage of cesium is recorded as A; the atomic percentage of the doped metal element is recorded as B, then B / (A+B)=0.35-0.45; The in-situ normalized luminescence intensity of the quantum dots after undergoing a 130° C. heating stage and a cooling stage can be restored to at least 80%.

2. The red perovskite quantum dot with high luminescence performance according to claim 1, characterized in that: The doping metal element is one or more of zinc, potassium, aluminum, magnesium, calcium, strontium, barium, sodium, rubidium, lithium, cerium, samarium, antimony, erbium, and bismuth.

3. The red perovskite quantum dots with high luminescence performance according to claim 1, characterized in that: The luminescence half-width of the quantum dots is less than 40nm, and there is only one luminescence peak, and the luminescence spectrum does not move or deform under blue light irradiation.

4. The red perovskite quantum dot with high luminescence performance according to claim 1, characterized in that: The micro / mesoporous template comprises a microporous material or a mesoporous material; The microporous material is one or more of microporous molecular sieve, microporous silica, microporous titanium dioxide, microporous alumina, microporous transition metal oxide, microporous sulfide, microporous silicate, microporous aluminate or microporous transition metal nitride; The mesoporous material is one or more of mesoporous molecular sieve, mesoporous silica, mesoporous titania, mesoporous alumina, mesoporous carbon, mesoporous transition metal oxide, mesoporous sulfide, mesoporous silicate, mesoporous aluminate or mesoporous transition metal nitride.

5. The red perovskite quantum dots with high luminescence performance according to claim 1, characterized in that: Also included is an isocyanate atmosphere within the shell.

6. The red perovskite quantum dot with high luminescence performance according to claim 1, characterized in that: The in-situ normalized luminescence intensity of the quantum dots after undergoing a 130° C. heating stage and a cooling stage can be restored to at least 90%.

7. The red perovskite quantum dot with high luminescence performance according to claim 5, characterized in that: The isocyanate atmosphere is generated by an isocyanate precursor at a high temperature, and the temperature range of the high temperature is greater than the collapse temperature of the micro / mesoporous template.

8. A perovskite quantum dot masterbatch, characterized in that: The perovskite quantum dot masterbatch comprises the red perovskite quantum dots according to any one of claims 1-7.

9. A perovskite quantum dot diffusion plate, characterized in that: The perovskite quantum dot diffusion plate comprises red perovskite quantum dots according to any one of claims 1-7.

10. A perovskite quantum dot film, characterized in that: The perovskite quantum dot film comprises the red perovskite quantum dots according to any one of claims 1-7.

Citation Information

Patent Citations

  • Preparation method and application of cyanuric acid coated halogen perovskite nano mixed crystal

    CN113913180A

  • Perovskite quantum dot, preparation method thereof and quantum dot device

    CN114316969A

  • Perovskite quantum dot and preparation method and application thereof

    CN114686218A

  • In-situ lead halide perovskite quantum dot diffusion plate and preparation method and application thereof

    CN116285138A